2014
DOI: 10.1016/j.ejpn.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

European study of frequency of participation of adolescents with and without cerebral palsy

Abstract: Children with cerebral palsy participate less in everyday activities than children in the general populations. During adolescence, rapid physical and psychological changes occur which may be more difficult for adolescents with impairments.Within the European SPARCLE project we measured frequency of participation of adolescents with cerebral palsy by administering the Questionnaire of Young People's Participation to 667 adolescents with cerebral palsy or their parents from nine European regions and to 4666 adol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 36 publications
3
76
1
3
Order By: Relevance
“…The higher perceived autonomy from parents in adolescents with PD compared to their peers without PD was at first sight counterintuitive and differed from previous findings (e.g., Everts et al 2008;Michelsen et al 2014). As the difference observed between the groups was based on the higher percentage of students with PD living away from their parents during term time, our results indicate that spending less time with parents increases perceived autonomy.…”
Section: Discussioncontrasting
confidence: 77%
See 3 more Smart Citations
“…The higher perceived autonomy from parents in adolescents with PD compared to their peers without PD was at first sight counterintuitive and differed from previous findings (e.g., Everts et al 2008;Michelsen et al 2014). As the difference observed between the groups was based on the higher percentage of students with PD living away from their parents during term time, our results indicate that spending less time with parents increases perceived autonomy.…”
Section: Discussioncontrasting
confidence: 77%
“…For example, Blum and colleagues (1991) found that many adolescents with PD were highly dependent on their parents for personal care. In accordance with this result, adolescents with PD reported less autonomy than adolescents without motor impairment (Everts et al 2008;Michelsen et al 2014). Adolescents with PD were also significantly less likely to have (paid) work experience than peers without PD (Anderson and Vogel 2000;Michelsen et al 2014) and scored significantly lower than able-bodied students on a measure of vocational development (Goldberg 1989).…”
Section: Peculiarities Of the Attainment Of Developmental Tasks In Adsupporting
confidence: 83%
See 2 more Smart Citations
“…Participation is generally significantly restricted as a result of cerebral palsy but this varies according to environmental factors as well as the severity of the condition [27]. Improvement in mobility resulting from effective treatment should lead to an improvement in participation.…”
Section: Quality Of Lifementioning
confidence: 99%